Analysis of Motion Simulation and Structure Design of the Reversing Device of New Pumping Unit - Liu Yongping; Dong Changbin; An Jianmin; Wang Xiumei (Jixie chuandong)
Aiming at the required characteristic such as long-stroke and low-velocity of the existing pumping unit,on the basis of analyzing the advantages and disadvantages of the traditional pumping units,the planetary gear train of non-circular gear are applied on the pumping unit reversing device. The structure of two kinds of reversing devices are analyzed and compared,and ADAMS simulation software is used to analyze the kinematics simulation. The angular,angular velocity and angular acceleration of two kinds of mechanism are obtained respectively. Through the comparative analysis,the conclusion that the two pairs of circular gears and two pairs of non-circular gear combination structure has more advantages than four pairs of non-circular gear structure are obtained.